2002
DOI: 10.1021/ja020407z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Polyoxometalates:  Electron and Proton Affinity of Mixed-Addenda Keggin and Wells−Dawson Anions

Abstract: A series of systematic DFT calculations were conducted on Keggin [SiW(9)M(3)O(40)](n-), M = Mo, V, and Nb; and Wells-Dawson anions [P(2)M(18)O(62)],(6-) M = W and Mo; [P(2)M(15)M(3)'O(62)](m-), M = W and Mo, M' = W, Mo, and V to analyze the redox properties and the basicity of the external oxygen sites in polyoxometalates with nonequivalent addenda metals. The energy and composition of the lowest unoccupied orbitals, formally delocalized over the addenda atoms, determine the redox properties of a polyoxometala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
195
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(209 citation statements)
references
References 79 publications
11
195
0
3
Order By: Relevance
“…Our results indicate that the metal atoms are not distributed randomly in the mixed addenda Keggin anions. This observation is consistent with previous results from the literature, which indicate that W atoms as well as other early transition metals substitute preferentially at the crown sites of mixed Keggin POMs [7,24,57,58]. The formation of segregated islands of W within mixed addenda POMs may explain the non-statistical behavior presented in Figure 4.…”
Section: Stability Of the Lindqvist Anionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results indicate that the metal atoms are not distributed randomly in the mixed addenda Keggin anions. This observation is consistent with previous results from the literature, which indicate that W atoms as well as other early transition metals substitute preferentially at the crown sites of mixed Keggin POMs [7,24,57,58]. The formation of segregated islands of W within mixed addenda POMs may explain the non-statistical behavior presented in Figure 4.…”
Section: Stability Of the Lindqvist Anionsupporting
confidence: 92%
“…These results indicate that regardless of the charge state, the electron binding energy of W 12 POM is higher than that of Mo 12 POM. In addition, Poblet and co-workers demonstrated that the energy of the LUMO is substantially decreased when only one W atom in the W 12 POM is replaced with Mo [24]. It is reasonable to assume that the electron binding energies of the mixed addenda POMs described herein fall between these two extremes.…”
Section: Competition Between Fragmentation and Charge Lossmentioning
confidence: 82%
See 2 more Smart Citations
“…49 If, on the one hand, static QM calculations have proven essential to investigate intrinsic properties such as structural stability, 50-55 electronic structure, [56][57][58][59][60] reactivity, 61,62 and spectroscopic signature; 63 it is equally true that classical MD simulations of Keggin salt solutions are an obligatory choice if one wishes to better elucidate their dynamic properties at the nanoscale. As such, their use alongside experiment is becoming increasingly common.…”
Section: Introductionmentioning
confidence: 99%